2016
DOI: 10.1038/bmt.2015.330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non-relapse mortality and causes of death over 15 years following allogeneic hematopoietic stem cell transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) has curative potential against hematological malignancies. However, there are concerns about the associated risk of non-relapse mortality (NRM). We performed a retrospective single-center study to assess changes in outcomes after allo-HSCT and causes of NRM over three 5-year periods. The rates of 2-year NRM and overall survival (OS) were 16% and 59%, respectively. We found a significant decrease in NRM (P o 0.001), with 2-year NRM of 26, 14 and 9%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…In a separate study the nonrelapse mortality rate was 24% with 20.2% being attributed to GVHD . Nonrelapse mortality can also be due to infectious disease with an incidence between 0.3% and 3.3% for fungal infections . A similar mortality rate due to IFI was reported by Kontoyiannis et al of 3.4% overall following HSCT (both autologous and allogenic) but was higher in allogenic HSCT ranging between 5.8% and 8.1% in matched‐related donors and mismatched‐related donors with a 1‐year survival of 25.4% in patients with aspergillosis infections …”
supporting
confidence: 60%
See 1 more Smart Citation
“…In a separate study the nonrelapse mortality rate was 24% with 20.2% being attributed to GVHD . Nonrelapse mortality can also be due to infectious disease with an incidence between 0.3% and 3.3% for fungal infections . A similar mortality rate due to IFI was reported by Kontoyiannis et al of 3.4% overall following HSCT (both autologous and allogenic) but was higher in allogenic HSCT ranging between 5.8% and 8.1% in matched‐related donors and mismatched‐related donors with a 1‐year survival of 25.4% in patients with aspergillosis infections …”
supporting
confidence: 60%
“…Two major complications of HSCT are graft‐versus‐host disease (GVHD) and invasive fungal infections (IFI), both leading to major morbidity and mortality. Following allogenic HSCT, grade II‐IV acute GVHD and chronic GVHD occur in 38% to 46% and 37% to 43% of patients, respectively, with mortality rates ranging between 0.3% and 1.7% in acute and 0.8% and 2.5% in chronic cases . In a separate study the nonrelapse mortality rate was 24% with 20.2% being attributed to GVHD .…”
mentioning
confidence: 89%
“…Although a recent trend analysis suggested that incidences of aGVHD and cGVHD following allogeneic HSCT have decreased in recent years [49], GVHD continues to pose a significant burden to transplant success and represents a leading cause of NRM [8,18,19]. The three REACH trials comprise the largest and most comprehensive prospective clinical trials to date evaluating a JAK1/JAK2 inhibitor in GVHD settings.…”
Section: Discussionmentioning
confidence: 99%
“…The additional cost for CAR-T therapy is also high, which may prevent its more widespread use in the near future. Allo-HSCT is good option for some patients because the morbidity and mortality from allo-HSCT is not insignificant, however, we must pay attention to the potential GVHD complications [44].…”
Section: Toxicitiesmentioning
confidence: 99%